THE EFFECT OF ADDITIONAL COMPENSATION ON EMPLOYEE PERFORMANCE THROUGH WORK MORALE AT PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Savira, Sarah; Khair, Hazmanan (Proceeding International Seminar of Islamic Studies, 2024)
Quality human resources will help advance the company as a forum for improving good performance. Therefore, a company should provide positive direction to its human resources in order to achieve the goals set by the company. Many factors influence performance, including additional compensation and work morale. The purpose of this research is to analyze several things, namely: to find out whether there is an effect of additional compensation on employee performance, to find out whether there is an effect of additional compensation on work morale, to find out whether there is an effect of work morale on employee performance and to find out whether additional compensation has an effect on performance which is mediated by enthusiasm for working at PT. Perkebunan Nusantara III (Persero) Medan. This research uses associative research with a sample of 87 respondents who are employees of PT. Perkebunan Nusantara III (Persero) Medan. Data collection techniques use a list of statements such as a questionnaire and data analysis techniques using Partial Least Square (SmartPls) to test the four hypotheses proposed in this research. The results of this research show that: (1) the effect of additional compensation on employee performance is positive and significant; (2) the effect of additional compensation on employee morale is positive and significant; (3) the effect of work morale on employee performance is positive and significant; (4) work morale as a mediator variable plays a mediating role in the effect of additional compensation on employee performance.